Does forced solidarity hamper investment in small and micro enterprises? - Michael Grimm; Renate Hartwig; Jann Lay (Institute for the Study of Labor (IZA), 2013)
Sharing is a norm in many societies. We present a theoretical model on the trade-off between sharing and investment which we test on data from tailors in Burkina Faso. The empirical results support the idea that there are two behavioural patterns: entrepreneurs following an 'insurance regime' comply with sharing norms, are insured but reduce investment in their firm, whereas entrepreneurs in the 'growth regime' are not insured but take undistorted investment decisions. The choice of regime depends on the redistributive pressure, the willingness to take risk, and the return on investment.
Keywords: D13; D22; D92; O12; O43; 330; forced solidarity; informal insurance; investment; micro and small enterprises; sharing; Sub-Saharan Africa